Perancangan Objective Structured Clinical Examination (OSCE) untuk Menilai Kompetensi Klinik - Zulharman Zulharman (Jurnal Ilmu Kedokteran, 2011)
When planned and organized correctly, OSCE can be highly successful as an instrument to assess competence inmedicine. Knowledge about how to plan and organize OSCE is required by OSCE’s designers in medical education, sothat OSCE which had been designed become valid, reliable and feasible. The elements in designed OSCE consisted ofdefining of clinical competency which be assessed, design station, patient, examiners, pass or fail scoring, logistics andcosts.